2016
DOI: 10.1021/acs.jnatprod.6b00554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Koumine on Adjuvant- and Collagen-Induced Arthritis in Rats

Abstract: To examine the effect of koumine, a Gelsemium alkaloid, on two experimental models of rheumatoid arthritis (RA), rats with adjuvant-induced arthritis (AIA) and collagen-induced arthritis (CIA) were administered koumine (0.6, 3, or 15 mg/kg/day) or vehicle through gastric gavage (i.g.). Clinical evaluation was performed via measurements of hind paw volume, arthritis index (AI) score, mechanical withdrawal threshold, organ weight, and by radiographic and histological examinations. Levels of interleukin (IL)-1β, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…Koumine (KM), the most abundant alkaloid in Gelsemium elegans Benth. ( G. elegans ) has various pharmacological properties and is known to be effective in the treatment of numerous age-associated conditions including postoperative pain ( Xiong et al., 2017 ; Shoaib et al., 2019 ), inflammation ( Yuan et al., 2016 ; Wu et al., 2020 ), rheumatoid arthritis ( Yang et al., 2016 ), malignant tumors ( Yuan et al., 2019a ), nonalcoholic fatty liver disease ( Yue et al., 2019 ), oxidative stress ( Yuan et al., 2019b ), and neuropathic pain ( Jin et al., 2018a ; Jin et al., 2018b ). However, the pharmacokinetic profile of KM in the elderly or aged animals remains to be fully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Koumine (KM), the most abundant alkaloid in Gelsemium elegans Benth. ( G. elegans ) has various pharmacological properties and is known to be effective in the treatment of numerous age-associated conditions including postoperative pain ( Xiong et al., 2017 ; Shoaib et al., 2019 ), inflammation ( Yuan et al., 2016 ; Wu et al., 2020 ), rheumatoid arthritis ( Yang et al., 2016 ), malignant tumors ( Yuan et al., 2019a ), nonalcoholic fatty liver disease ( Yue et al., 2019 ), oxidative stress ( Yuan et al., 2019b ), and neuropathic pain ( Jin et al., 2018a ; Jin et al., 2018b ). However, the pharmacokinetic profile of KM in the elderly or aged animals remains to be fully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the analgesic effect of koumine in various animal pain models, such as chronic constriction injury (CCI), spared nerve injury, diabetic NP, and rheumatoid arthritis pain models (Xu et al, 2012; Ling et al, 2014; Qiu et al, 2015; Yang et al, 2016; Xiong et al, 2017; Jin et al, 2018a). Koumine displayed high efficiency and low toxicity in the treatment of NP, implying that this compound may have potential as a new anti-NP drug.…”
Section: Introductionmentioning
confidence: 99%
“…Several potential pharmaceutical roles for koumine have been identified, including anxiolytic, antitumor, antistress, antipsoriatic, and analgesic activities [ 14 18 ]. In previous studies, we found that koumine plays a significant role in the anti-inflammatory and analgesic effects in inflammatory and NP models [ 18 21 ]. Interestingly, both the anxiolytic and analgesic effects of koumine may involve the modulation of neurosteroids in the spinal cord [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%